Attachment representations in individuals diagnosed with schizophrenia: A projective study through the bird’s nest drawing - Demir, Volkan (The European Research Journal, 2025)
Objectives: This study aims to explore the attachment representations of individuals diagnosed with schizophrenia through the Bird’s Nest Drawing, a projective technique. It also seeks to compare the findings with those of individuals without a schizophrenia diagnosis to identify potential differences in attachment-related imagery and narrative themes. Methods: A total of 100 participants took part in the study: 50 individuals diagnosed with schizophrenia and 50 without any psychiatric diagnosis. Each participant was asked to draw a bird’s nest and write a brief narrative about their drawing. Quantitative data were analyzed using chi-square tests. Qualitative analysis was conducted through thematic evaluation of narratives from 15 randomly selected participants from each group. Results: Quantitative analysis showed statistically significant group differences in several aspects of the drawings, including the presence of parent bird and chick/egg, use of appropriately colored figures, frequent use of green, and whether the nest touched a surface. Qualitative analysis revealed that narratives of individuals with schizophrenia included themes of loneliness, mistrust, unmet basic needs, and disconnection from the nest. Conversely, narratives of individuals without schizophrenia reflected familial closeness, caregiving, and emotional security. Conclusions: The results suggest that individuals with schizophrenia project attachment-related difficulties - such as distrust, disconnection, and impaired bonding - more prominently in both their drawings and written narratives. The BND test appears to be a meaningful tool for exploring attachment dynamics at the projective level in clinical populations.